Pengaruh Faktor Demografi terhadap Status Merokok Remaja sebagai Dampak Alokasi Dana Bagi Hasil Cukai Hasil Tembakau (DBHCHT) - Sukmono, Renny (Politeknik Keuangan Negara STAN, 2019)
ABSTRAKÂ The number of smokers in Indonesia is increasing year by year. Along with the increase in the number of smokers, the proportion of teenage novice smokers is also increasing. The number of teenage smokers in Indonesia is still very large and dominated by boys. There are many factors behind why teenagers smoke. In this study, demographic factors including gender, parents 'smoking status, parents' economic status, education of parents and adolescent areas living (divided into two, namely DBHCHT recipient areas and not CHT DBH recipients) are used. Profit sharing from tobacco products (DBH CHT) is funds allocated to finance certain activities related to goods that have characteristics which consumption needs to be controlled and monitored and has negative impacts on the community. The data used in this study are secondary data sourced from the 2013 Indonesian Basic Health Research survey conducted by the Ministry of Health. Observations were made on 86.810 boys and 79.745 girls. The analytical method used is logistic regression analysis. Based on the results of the analysis it was found that teenagers smoking learn from what they see in the environment in which they are located. If there is one parent who smokes, the teenagers tends to smoke too. This tendency is even greater if both parents smoke. Likewise, with areas with more